ASEAN bibliography of selected libraries in Metro Manila - Santiago, Joseph Sedfrey S. (Quezon City Institute of International Legal Studies, University of the Philippines Law Center, 1997)
A bibliography of materials on different aspects of ASEAN, from the arts to trade, located in 18 academic, special, public and government libraries in Metro Manila. The listing is arranged by subject, and then chronologically, by year of publication. It provides the title, author, and the code of the library in which the material may be found. Years of publication of materials range from 1970 to 1996.
Keywords: Association of Southeast Asian Nations -- Bibliography -- Philippines -- Manila Metropolitan area; Asia, Southeastern -- Philippines -- Manila Metropolitan area. -- Bibliography; Asia, Southeastern -- Library resources -- Philippines -- Manila Metropolitan area